A comparison of nasopharyngeal endoscopy and lateral cephalometric radiography in the diagnosis of nasopharyngeal airway obstruction - Ianni Filho, Daniel; Raveli, Dirceu Barnabé [UNESP]; Raveli, Rosangela B.; De Castro Monteiro Loffredo, Leonor [UNESP]; Gandini Jr., Luiz G. [UNESP] (Elsevier, 2001)
Two auxiliary methods of diagnosing nasopharyngeal airway obstruction were compared. Cephalometric radiography and nasopharyngeal videoendoscopy were evaluated for efficacy in terms of reproducibility and validity. Thirty orthodontic patients (7 to 12 years of age) seeking otorhinolaryngologic treatment for mouth breathing, or mouth and nose breathing, had nasopharyngeal endoscopy and radiographic examinations performed on the same day. Two otorhinolaryngologists analyzed the results. Nasopharyngeal endoscopy was more reliable in identifying all the obstructive nasopharyngeal processes. Endoscopy obtained kappa index scores of almost perfect agreement for diagnosis of posterior nasal septum deviation, of substantial agreement for anterior nasal septum deviation and lower turbinate hypertrophy, and of moderate agreement for middle turbinate hypertrophy. Lateral cephalometric radiography obtained scores of perfect agreement for imaging hypertrophy of the middle turbinate, of almost perfect agreement for imaging hypertrophy of the posterior portion of the inferior turbinate, and of substantial agreement for imaging hypertrophy of the inferior turbinate. Radiographic diagnoses of hypertrophy of the middle and lower turbinates exhibited high sensitivity and low specificity when compared with diagnoses by nasopharyngeal endoscopy.
Keywords: cephalometry; child; clinical trial; comparative study; controlled clinical trial; controlled study; endoscopy; female; human; male; methodology; mouth breathing; nasopharynx; nose obstruction; nose septum; observer variation; pathology; radiography; reproducibility; rhinitis; sensitivity and specificity; single blind procedure; turbinate; videorecording; Cephalometry; Child; Endoscopy; Female; Humans; Male; Mouth Breathing; Nasal Obstruction; Nasal Septum; Nasopharynx; Observer Variation; Reproducibility of Results; Rhinitis; Sensitivity and Specificity; Single-Blind Method; Turbinates; Video Recording